Increased NRG1-ErbB4 signaling in human symptomatic epilepsy - Jun-Ming Zhu (Nature Portfolio, 2017)
Abstract Previous studies have shown that the neuregulin 1 (NRG1)-ErbB4 signaling pathway may regulate the excitability of fast-spiking neurons in the frontal cortex and participate in primary epilepsy pathogenesis. However, the exact roles and mechanism for NRG1/ErbB4 in human symptomatic epilepsy are still unclear. Using fresh human symptomatic epilepsy tissues, we found that the protein levels of NRG1 and ErbB4 were significantly increased in the temporal cortex. In addition, NRG1-ErbB4 signaling suppressed phosphorylation of GluN2B at position 1472 by Src kinase, and decreased levels of phosphorylation level of GluN2B and Src were detected in human symptomatic epilepsy tissues. Our study revealed a critical role of the NRG1-ErbB4 signaling pathway in symptomatic epilepsy, which is different from that in primary epilepsy, and we propose that the NRG1-ErbB4 signaling may act as a homeostasis modulator that protects the brain from aggravation of epileptiform activity.